Taxonomic characterizations of the genus Commicarpus Standl. (Nyctaginaceae) in Saudi Arabia - Maad S. Ytemi; Hameed Alsamadany; Faraj Abdullah Al-Ghamdi; Abadi M. Mashlawi; A. El-Shabasy (PLoS ONE, 2026)
The genus Commicarpus Standl. is a member of the family Nyctaginaceae. The genus includes about 30–35 species distributed across tropical and subtropical regions worldwide, including Saudi Arabia. Five species of Commicarpus are found through, the field survey, which are primarily concentrated in the western and southwestern regions of Saudi Arabia. The collected species are C. grandiflorus , C. helenae , C. mistus , C. plumbagineus , and C. sinuatus . The aim of this study is to do morphological, anatomical, and palynological analyses of these species. Morphologically, growth habit, stem texture, leaf characteristics, floral structure, and fruit morphology were evaluated, these characters are significant to distinguish Commicarpus species. Anatomical studies of the stems, leaves, and petioles show some important characteristics that can help to separate Commicarpus species, including variations in collenchyma and chlorenchyma layers, vascular bundle arrangement, and mesophyll structure. Petiole anatomy, particularly the shape and arrangement of ground tissue and vascular bundles, provides additional taxonomic markers. Also, the study of pollen grains of the species using light microscopes (LM) and scanning electron microscopes (SEM) provides significant character that can be used for species differentiation, including differences in pollen size, shape, polar and equatorial axis dimensions, tubuliferous density, pore diameter, and spinule length. Pollen grains are very large in C. grandiflorus , C. plumbagineus , and C. sinuatus and large in C. helenae and C. mistus ; their shapes range from oblate-spheroidal in C. grandiflorus to prolate-spheroidal in the other species. Two keys are constructed, one utilizing morphological characteristics and the other employing anatomical features of the petioles to aid in species identification. These results contribute valuable taxonomic information for the genus Commicarpus in Saudi Arabia.